Mathematics teachers’ perspectives on utilizing AI in their teaching practices: Examining regional and teaching experience factors - El-Shara, Ibrahim; Abu-Ghalyoun, Omar; Arouri, Yousef; Jbareen, Hanan (Journal of Education and e-Learning Research, 2025)
This study aimed to explore mathematics teachers’ perceptions of using AI in their teaching. A sample of 307 mathematics teachers from the University Directorate and the Hifa Educational Region was selected using simple random sampling. Data were collected through a structured questionnaire, specifically designed and psychometrically validated. The study results showed that mathematics teachers’ perceptions of using AI tools in their practices were above average overall, and in the subdomains of lesson planning, instructional practices, and students' assessment. However, their perceptions revealed a deep awareness of the challenges that hinder the effective integration of these tools, indicating a dire need for specialized training on the use of AI tools, appropriate classroom infrastructure, and ethical guidelines or policies. Although the study found significant differences in perceptions based on the geographic region, favoring the Haifa region, there were no significant differences related to teachers’ experience. This study offered recommendations to help educational decision-makers adopt educational reforms that promote the wise use of AI tools. This aims to improve the effectiveness of teaching mathematics and boost student performance. It also adds to the existing literature by supporting previous studies’ evidence on mathematics teachers’ perceptions of using AI in their practices and providing further empirical support.